The controversy of the 2013 severe water disruptions in Selangor, Malaysia: a critical analysis - Ithnin Hamirdin, Mokmin Mujirah, Sakke Nordin, (N/A, 2014)
The controversy of the 2013 severe water disruptions in Selangor, Malaysia: a critical analysis by Ithnin Hamirdin, Mokmin Mujirah, Sakke Nordin,